Ultimate avengers 2 Rise of the Panther. - Johnson, Greg,|d1953-.; Kyle, Craig; Michelmore, Guy.; Millar, Mark.; Hitch, Bryan; Lions Gate Films; Marvel Entertainment Group; Marvel Comics Group; Lions Gate Entertainment (Firm).; Viva Video (Santa Monica, Calif. Lions Gate Home Entertainment; distributed in the Philippines by Viva Video, 2006)
To save humanity, the Earth's mightiest heroes must reunite for a rematch of heroic proportions.
Based upon Marvel Comics' The ultimates, by Mark Millar and Bryan Hitch ; Captain America based upon the Marvel Comic by Joe Simon and Jack Kirby.
Producer and supervising director, Bob Richardson; editor, George P. Rizkallah ; music, Guy Michelmore.
Voices: Justin Gross, Grey DeLisle, Michael Massee, Marc Worden, Olivia D'Abo, Nan McNamara, Nolan North, Andre Ware, Dave Boat, Fred Tatasciore, James K. Ward.
MPAA rating: PG-13; for intense action violence.
VCD
Keywords: Captain America -- (Fictitious character) -- Drama; Incredible Hulk -- (Fictitious character) -- Drama; Iron Man -- (Fictitious character) -- Drama; Iron Man -- (Fictitious character) -- Drama; Animated films; Superhero films